Features of plankton community in the Chukchi Sea in August-September, 2017 - N. A. Kuznetsova (Известия ТИНРО)
Zooplankton in the eastern Chukchi Sea is described on the data of summer observations in 2017. The northern part of the surveyed area was occupied by the cold water masses from the Arctic Ocean and Beaufort Sea. Large-sized zooplankton dominated here, including copepods Calanus glacialis, C. hyperboreus (this species is an indicator of Atlantic waters) and cold-water hyperiids Themisto libellula. In the southern part of the surveyed area, small-sized zooplankton dominated by biomass and abundance and species belonged to the Bering Sea community, as copepods Calanus glacialis + Calanus marshallae, Eucalanus bungii, and Metridia pacifica, were presented in the large-sized fraction. In the western part of the surveyed area and in the coastal waters, small-sized copepods Pseudocalanus spp. and Oithona similis prevailed, and biomass and abundance of neritic species as Centropages abdominalis and Acartia longiremis were high, too. Besides, some species typical for desalinated water were observed here (Eurytemora herdmani, Podon sp., and Epilabidocera amphitrites), as well as larval forms of benthic invertebrates (larvae of polychaetes, bivalves, gastropods, and echinoderms). Arrowworms Sagitta elegans were abundant everywhere that was caused by this species reproduction. The observed structure of plankton community corresponded to feeding demands of arctic cod juveniles, but the zooplankton biomass was rather low. These features of community could be interpreted as early summer state, when its biomass does not reach the maximum yet, as it was observed, for example, in September 2007.